2023
DOI: 10.3332/ecancer.2023.1515
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to cancer care in Rwanda: the role of tumour board meetings

Abstract: Introduction: Cancer treatment is complex and necessitates a multidisciplinary approach. Tumour Board Meetings (TBMs) provide a multidisciplinary platform for health care providers to communicate about treatment plans for patients. TBMs improve patient care, treatment outcomes and, ultimately, patient satisfaction by facilitating information exchange and regular communication among all parties involved in a patient's treatment. This study describes the current status of case conference meetings in Rwanda inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These approaches are similar to clinical ethics resolutions used in different settings globally. (22,23) Unlike the structured clinical ethics consultation services prevalent in developed nations, fora utilized to resolve ethical dilemmas at the UCI, while integral to their established roles, have been scrutinized for their implicit and non-ethics-focused nature. While these existing platforms serve their intended purposes, they fall short in adequately resolving complex ethical issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches are similar to clinical ethics resolutions used in different settings globally. (22,23) Unlike the structured clinical ethics consultation services prevalent in developed nations, fora utilized to resolve ethical dilemmas at the UCI, while integral to their established roles, have been scrutinized for their implicit and non-ethics-focused nature. While these existing platforms serve their intended purposes, they fall short in adequately resolving complex ethical issues.…”
Section: Discussionmentioning
confidence: 99%
“…This collaborative approach mirrors practices in Rwanda, Kenya, and Botswana, where similar strategies are employed in cancer settings to address complex dilemmas within cancer wards. (23,(29)(30)(31) Intriguingly, only a minimal number of respondents in this study experienced this collaborative approach. Notably, the tumor board meetings were not primarily convened for ethical and moral case deliberations.…”
Section: Tumor Board Meetingsmentioning
confidence: 92%
“…This is supported by the results published by Ntakiyiruta who carried out an assessment of gastric cancer at Kibogora hospital and found that the majority of the cancers cases were diagnosed at an advanced stage due to the fact that the early stomach cancers do not show any specific symptoms and endoscopic screening were not easily accessible 18 . The study that was conducted by Niyibizi and colleagues in 2023 revealed that the patients in lower and middle income countries including Rwanda often present to the health facilities and cancer centers with more advanced cancer that require multimodality treatment for better clinical outcomes 19 . The diagnosis of cancer cases that is done at advanced stage was also highlighted by Rubagumya and his colleagues noting that the increment of cancer awareness in the general population is a great necessity to encourage them to shift to early diagnosis, hence effective treatment and better clinical outcomes 20 .…”
Section: Discussionmentioning
confidence: 99%